Effect of Indirect Neural Decompression with Oblique Lateral Interbody Fusion Was Influenced by Preoperative Lumbar Lordosis in Adult Spinal Deformity Surgery - Tan Boon Beng; Yoshihisa Kotani; Ung Sia; Ivan Gonchar (Asian Spine Journal, 2019)
Study Design Retrospective clinical study on the indirect decompressive effect of oblique lateral interbody fusion (OLIF) for adult spinal deformity. Purpose To evaluate the effect of interbody distraction by OLIF for the treatment of adult spinal deformity. Overview of Literature Adult spinal deformity with symptomatic stenosis has been addressed conventionally using a direct posterior decompression approach with fusion. However, stenotic symptoms can also be alleviated indirectly through restoration of intervertebral and foraminal heights and correction of spinal alignment. Methods Twenty-eight patients with adult spinal deformity underwent OLIF combined with modified cortical bone trajectory screws at 94 lumbar levels with neuromonitoring. The patients were divided into three groups based on their preoperative lumbar lordosis: group A, <0°; group B, 0°–20°; and group C, >20°. The cross-sectional area (CSA) of the thecal sac was measured preoperatively and postoperatively on axial magnetic resonance images. Differences in CSA were evaluated, and the relationship between the CSA extension ratio and preoperative CSA was assessed. Changes in disc height and segmental disc angle were measured from plain radiographs. Results OLIFs were performed successfully without neural complications. In group A, the mean CSA increased from 120.6 mm2 preoperatively to 148.5 mm2 postoperatively (p <0.001). The mean CSA for group B increased from 120.1 mm2 preoperatively to 154.4 mm2 postoperatively (p <0.001). Group C had an increase in mean CSA from 114.7 mm2 preoperatively to 160.7 mm2 postoperatively (p <0.001). The mean CSA enlargement ratio was 27.5%, 32.1%, and 60.4% in groups A, B, and C, respectively. The mean CSA extension ratio was inversely correlated with preoperative CSA. Conclusions The effect of indirect neural decompression in adult spinal deformity with OLIF varies with the degree of preoperative lumbar lordosis.